M1 macrophage-derived exosomal miR-20b promotes radiosensitization via CCND1 in HPV+ HNSCC - Liu, Huan; Zhang, Siwei; Liu, Zengchen; Gong, Tingdan; Duan, Siyu; Liu, Tianyang; Tong, Fangjia; Li, Wanlin; Pan, Shuang; Wei, Lanlan (Frontiers in Oncology, 2025)
BackgroundHuman papillomavirus (HPV) is a significant risk factor for head and neck squamous cell carcinoma (HNSCC). HPV positive (HPV+) HNSCC is more sensitive to radiotherapy and has a better prognosis than HPV negative (HPV-) HNSCC. M1 macrophages not only enhance the radiosensitivity of HPV+ HNSCC, but the M1 macrophages derived exosmoes (M1 exos) also possess anti-tumor activity. However, the role of M1 exos in the radiosensitivity of HNSCC remains unclear.Materials and methodsHPV status and macrophage infiltration levels in 25 HNSCC tissues were evaluated by immunohistochemistry (IHC). M1 macrophages were induced and cultured in vitro, and exosomes were extracted through differential ultracentrifugation. The effect of M1 exos on the radiosensitivity of HPV+ HNSCC was assessed via an in vitro co-culture system. The expression level of γ-H2AX was assessed by immunofluorescence. The levels of miR-20b in HNSCC were analyzed using multicenter data (from TCGA and GEO databases), along with their correlation to radiosensitivity and prognosis. Cellular experiments demonstrated that overexpressing miR-20b significantly enhanced radiosensitivity in HPV+ HNSCC. Bioinformatic and experimental validation identified CCND1 as a target of miR-20b.ResultsIn HPV+ HNSCC, M1 macrophages were highly infiltrated and played a crucial role in improving the therapeutic effect of HPV+ HNSCC. M1 exos infiltrated HPV+ HNSCC, increasing their sensitivity to radiation. Meanwhile, M1 macrophages exhibited higher miR-20b levels than M2 macrophages, and the radiosensitivity of HPV+ HNSCC was significantly increased by transfecting them with a miR-20b mimic. Functional analysis of target genes, CCND1 as a key gene through which miR-20b enhanced radiosensitivity in HPV+ HNSCC.ConclusionIn this study, our results suggest that M1 exos, enriched with miR-20b, regulate the DNA damage repair pathway in tumor cells by targeting CCND1, enhancing the radiosensitivity of HPV+ HNSCC.